Singgora tiles : perception of the community in Kota Bharu, Kelantan / Nor Hidayah Abdullah, Rodiah Zawawi and Zuraini Md Ali - Abdullah, Nor Hidayah; Zawawi, Rodiah; Md Ali, Zuraini (Faculty of Architecture, Planning & Surveying, 2015)
Plain tile, locally known as Singgora tile, is a type of traditional tile that has been widely used in Kelantan as a roof covering before the advent of modern roofs. With the passage of time, these tiles are now almost forgotten and most of the buildings that still use it are old buildings and newly constructed traditional buildings. The goal of this study is to find out community perceptions towards Singgora tiles by the age of the community members, and analysing the potential for demand for Singgora tiles to develop in the market. In this study, it has been concluded that users agreed on the advantage of Singgora tiles in providing a cool indoor temperature in the house, but the product is easily broken. The majority of users turn to other types of roof covering because of the limited supply of Singgora tiles. However most users are interested in using Singgora tiles if the quality is improved. With regards to the new generation, the awareness of the existence of this traditional tile decreases with age.